Multitemporal water quality analysis of a karst spring affected by allogenic recharge - Cahyadi, Ahmad (American Institute of Physics Inc., 2023)
This research aimed to study the multitemporal water quality of a karst spring affected by allogenic recharge. Allogenic refers to water from adjacent non-karstic regions that replenish karst groundwater through ponors. Research samples were collected for a year at Gremeng Resurgence, the outlet of Gremeng Karst Drainage Basin. The water quality analysis compared the laboratory test outcomes and measurements with existing drinking water quality standards and included hydrogeochemical studies using both trilinear and rectangular Piper plots. The analysis results indicate that rainwater causes dilution; hence, parameter values are relatively low in the rainy season but high in the dry season. Despite this variation, the groundwater at the Gremeng Resurgence meets the quality standards throughout the year. The Piper diagram analysis classifies it as unpolluted, calcium-enriched, average bicarbonate, and bicarbonate groundwater, supporting the finding. © 2023 Author(s).